Critical race theory matters : education and ideology - Zamudio, Margaret, 1964-2009; Russell, Christopher; Rios, Francisco, 1956-; Bridgeman, Jacquelyn L. (Taylor & Francis, 2010)
Over the past decade, Critical Race Theory (CRT) scholars in education have produced a significant body of work theorizing the impact of race and racism in education. "An Introduction to Critical Race Theory in Education" traces the history of CRT, ultimately providing a comprehensive and accessible overview of this influential movement. The authors detail and synthesize scholarship in the field, highlighting the assumptions and major themes in clear and accessible language. By linking theory to everyday practices in today's classroom, students will understand how CRT is being applied to a host of timely topics, such as tracking, high-stakes testing, and school financing. Concluding with an examination of strategies of resistance and practices for challenging the existing inequalities in education, this book proves to be a valuable resource for all students who are interested in understanding how CRT applies to everyday practices.